Public Relations Management in Improving School Quality at Ar-Risalah Islamic Boarding School - Fira Nur Anisa; Mutia El Ilmi Putri Nasution (ISTIFHAM, 2025)
This study analyses the role of public relations management in improving school quality at Madrasah Aliyah Ar Risalah Padang. This Islamic educational institution continues to adapt to the development of digital communication in the era of society 5.0. Using a qualitative design with sociological and anthropological approaches, this research applies digital content analysis to the institution’s official website and Instagram publications from 2019 to 2024, combined with relevant literature. The theoretical framework integrates three perspectives, namely Digital Public Relations by Kent and Taylor, Total Quality Management, and Image Restoration Theory by Benoit. Through these perspectives, the study explores how public relations contributes to institutional communication, quality assurance, and the strengthening of reputation. The findings show that the public relations division plays a central role in fostering transparent communication, sustaining continuous interaction with stakeholders, enhancing teacher professionalism, and disseminating student achievements that support institutional branding. Public relations practices at Ar Risalah also enhance the institution’s ability to respond to issues by fostering openness and implementing corrective measures that maintain public trust. This study concludes that integrated public relations management functions as a strategic instrument for enhancing school quality while positioning Ar Risalah as a competitive model for digitally oriented Islamic education.